Carvacrol delays Phomopsis stem-end rot development in pummelo fruit in relation to maintaining energy status and antioxidant system. (15th March 2022) - Chen, Chuying; Cai, Nan; Wan, Chunpeng; Kai, Wenbin; Chen, Jinyin
Highlights: Phomopsis stem-end rot (SER) is a severe fungal disease caused by Diaporthe citri . Carvacrol (CVR) attenuates D. citri growth and Phomopsis SER development. CVR delays firmness loss and maintains cellular ATP homeostasis. CVR promotes ROS scavenging by elevating antioxidant system. Abstract: Pummelo fruit rapidly depreciate in commodity value due to postharvest fungal decay and fruit quality deterioration. Here, we used carvacrol (CVR) to control Phomopsis stem-end rot (SER) caused by Diaporthe citri in pummelo fruit stored at 25 °C. Antifungal activity of CVR inhibited D. citri growth and Phomopsis SER development. Harvested pummelo fruit treated with CVR delayed firmness loss and lowered electrolyte leakage, and retarded hydrogen peroxide (H2 O2 ) and malondialdehyde (MDA) accumulation. Unlike the control fruit, the CVR-treated fruit maintained higher levels of adenosine triphosphate and energy charge, and increased ATPase, succinate dehydrogenase (SDH), malate dehydrogenase (MDH), and cytochrome C oxidase (CCO) activities, along with up-regulated expression levels of the respective genes. CVR improved the antioxidant capacity, as evidenced by higher non-enzymatic antioxidants amounts, higher activities of superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), ascorbate peroxidase (APX) and glutathione reductase (GR), and up-regulated expression levels of ROS-scavenging-related genes. Collectively, CVR treatment maintained the energy status and antioxidant capacity in D. citri -infected pummelo fruit, which revealed antifungal mechanisms critical for controlling postharvest fungal diseases.